Understanding enabling levers of control (LOC) in Malaysian Local Government Authorities (LGAs) : The case of LGKV and LGER / Azmi Aminuddin - Aminuddin, Azmi (2016)
Malaysian LGAs (Local Government Authorities) are expected to establish high quality urban, social and recreation services; provide opportunities for uniform economic growth; be strong and able to contribute to the establishment of a progressive society and a clean and healthy environment. The new public sector management reforms movement has highlighted the importance that authorities use an appropriate MCS (Management Control System) as well as both financial and nonfinancial performance measurement in order to improve the ineffectiveness and inefficiency that was previously reported. By employing an inductive comparative case study using qualitative research techniques, the implementation of LOC (Levers of Control) and LOC:SSR-PBT Star Rating System was investigated in two selected Malaysian LGAs: LGKV and LGER. Using Institutional Theory as the underpinning theory, the phenomena of change that take place towards the implementation was also identified. The study found that there was a close connection between LOC and SSRPBT Star Rating System criteria where they more or less match each other in various ways, thus LOC:SSR-PBT Star Rating System was later used to provide a more systematic, thorough and deeper analysis. Both examination of the extent and nature of LOC and LOC:SSR-PBT Star Rating System implemented in both LGAs studied is observed to be in line. The differences in emphasis justify the nature of MCS which exists and they relate to the achievement of their star rating. In understanding the phenomena of change the study uses DiMaggio and Powell's (1983) framework to look at the institutional isomorphism in terms of the external forces penetrated to affect the change. It was found that there was a variation between the LGAs studied. Among the three forms of isomorphism (coercive, normataive and mimetic), the study found an obvious variation for LGKV and LGER in terms of normative isomorphism, whereby LGKV showed a strong external pressure whilst LGER is low. In relation to mimetic isomorphism, LGKV also had a strong external force whilst LGER was just moderate, whilst both experienced strong coercive pressures. Overall, the isomorphic forces was strong for LGKV and only moderate for LGER. Using Adler and Borys' (1996) framework, the study focusses on the internal force that enhances and provides energy to make the changes; concluded a different intensity of enabling formalization. Overall, the intensity for enabling formalization (repair, internal transparency, global transparency and flexibility) was found to be higher in most cases for LGKV rather than LGER, so overall it was generally high for LGKV and moderate for LGER. By means of Broadbent and Laughlin's (1998) context the study looks into the change absorption process. It was found that both LGAs had comparatively similar categories of absorption groups characteristics but different absorption process and rate. Majority of the staff were fully committed whilst minority were pessimistic and resisted group, however the change absorption rate was observed to be fast for LGKV and moderate for LGER. The variations in external and other internal forces were also found to have influenced the different rate. The study hopes that LGAs managers are able to induce the patterns of MCS that take place and then acquire the change insights so that whilst confronting the existence of external and internal forces, the performance of the authorities in financial and non-financial terms can be improved.